PEMBERDAYAAN PKK MELALUI BUDIDAYA APOTIK HIDUP (STUDI KASUS PADA PKK GEUDUBANG JAWA) - Murni, Mayang; Asnidar, Asnidar; Nafaida, Rizky (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity is motivated by the importance of utilizing, revitalizing, and optimizing existing potential and resources, then processing that potential into a finished product with added economic value, whose benefits will be felt by the PKK Geudubang Jawa, Langsa Baro District, Langsa City. The purpose of this activity is to increase the capacity of PKK members in three important aspects. First, to increase the knowledge and skills of members in managing the potential of village land in an organized and long-term manner, so that the land can become a resource with economic value. Second, to increase PKK productivity by providing knowledge and skills in processing raw materials from village land into finished products that are ready to be sold, so that the PKK can have independent output products. Third, to increase the economic independence of PKK members through entrepreneurship training, business management, and product marketing, to ensure economic sustainability for PKK Geudubang Jawa. The methods used include socialization, training, mentoring, and evaluation. The results of PKK empowerment activities through the cultivation of this living pharmacy have had a significant positive impact on community welfare in various aspects, both in terms of health, environmental management, and family economic empowerment. One of the significant economic impacts of this activity is the development of local products based on medicinal plants. From the cultivation of medicinal plants, members of the PKK Geudubang Jawa have succeeded in processing herbal tea products called Teh Rempah. This tea is a mixture of local spices such as ginger, lemongrass, turmeric, and galangal, which are processed into ready-to-brew herbal drink products. Teh Rempah is now a leading product sold in the local market and provides new economic opportunities for PKK members. Kegiatan pengabdian kepada masyarakat ini dilatarbelakangi oleh pentingnya memanfaatkan, merevitalisasi dan mengoptimalisasikan potensi serta sumber daya yang ada, kemudian mengolah potensi tersebut menjadi suatu produk jadi bernilai tambah ekonomis yang manfaatnya akan dirasakan oleh PKK Geudubang Jawa Kecamatan Langsa Baro, Kota Langsa. Tujuan kegiatan ini adalah untuk meningkatkan kapasitas anggota PKK dalam tiga aspek penting. Pertama, meningkatkan pengetahuan dan keterampilan anggota dalam mengelola potensi lahan desa secara terorganisir dan berorientasi jangka panjang, sehingga lahan dapat menjadi sumber daya bernilai ekonomis. Kedua, meningkatkan produktivitas PKK dengan memberikan pengetahuan dan keterampilan mengolah bahan baku dari lahan desa menjadi produk jadi yang siap dijual, sehingga PKK memiliki produk luaran yang mandiri. Ketiga, meningkatkan kemandirian ekonomi anggota PKK melalui pelatihan kewirausahaan, pengelolaan usaha, hingga pemasaran produk, untuk memastikan keberlanjutan ekonomi bagi PKK Geudubang Jawa. Metode yang digunakan meliputi sosialisasi, pelatihan, pendampingan dan evaluasi. Hasil kegiatan pemberdayaan PKK melalui budidaya apotek hidup ini telah memberikan dampak positif yang signifikan bagi kesejahteraan masyarakat diberbagai aspek, baik dari segi kesehatan, pengelolaan lingkungan, maupun pemberdayaan ekonomi keluarga. Salah satu dampak ekonomi yang signifikan dari kegiatan ini adalah pengembangan produk lokal berbasis tanaman obat. Dari hasil budidaya tanaman obat, anggota PKK Geudubang Jawa berhasil mengolah produk teh herbal yang dinamakan “Teh Rempah”. Teh ini merupakan campuran dari rempah-rempah lokal seperti jahe, serai, kunyit, dan lengkuas, yang diolah menjadi produk minuman herbal siap seduh. Teh Rempah kini menjadi produk unggulan yang dijual di pasar lokal, dan memberikan peluang ekonomi baru bagi para anggota PKK.